Unveiling Motivators: Why Economics Teachers at Tribhuvan University Embrace ICT in Teaching (Sotang, Yearly Peer Reviewed Journal, 2025)
This study explores the motivational factors driving economics teachers at Tribhuvan University to integrate Information and Communication Technology (ICT) into their teaching practices. Through a qualitative research design employing in-depth interviews with eight purposively selected teachers, the study identifies four key dimensions of motivation: perceived usefulness, student support, teaching excellence, and external influences. Teachers highlighted the potential of ICT tools to simplify complex economic concepts, enhance student engagement, and streamline teaching processes, thus improving instructional quality and relevance. External factors, including institutional policies, training opportunities, and societal expectations, further reinforce their adoption of ICT. Thematic analysis reveals that the integration of ICT not only enriches students' learning experiences through real-time, interactive, and personalized approaches but also supports continuous professional development and teaching excellence. These findings emphasize the importance of fostering a supportive ecosystem that combines professional development, institutional backing, and acknowledgment of teachers’ efforts to sustain and expand ICT adoption in higher education.